Association Between Thr21Met and Ser89Asn Polymorphisms of the Urotensin II Gene and Systemic Sclerosis - Pehlivan, Yavuz; Gogebakan, Bulent; Oztuzcu, Serdar; Ozgen, Metin; Cetin, Gozde Yildirim; Bayraktar, Recep; Onat, Ahmet Mesut (J Rheumatol Publ Co, 2012)
Objective. Systemic sclerosis (SSc) is an autoimmune chronic fibrotic disorder. Urotensin II (U-IT) is predominantly a vasoactive peptide with fibrotic and prothrombotic features. Like endothelin-1 (ET-1), U-II could play an important role in SSc pathogenesis. We evaluated the possible role of the U-II gene polymorphisms (Thr21Met and Ser89Asn) in the genetic susceptibility to SSc in a Turkish population. Methods. A total of 189 patients with SSc and 205 healthy controls were enrolled in our study. We analyzed the genotype and allele frequencies of the U-II (UTS2) gene polymorphisms Thr21Met and Ser89Asn in patients with SSc and in controls. Results. We found that the Thr21Met polymorphism of the UTS2 gene was markedly associated with the risk of developing SSc (p < 0.0001), but there was no relationship between the Ser89Asn polymorphism and SSc (p > 0.05). Two haplotypes (MS and TS) were markedly associated with SSc (p < 0.05). There were significant associations between the genotype and allele frequencies of UTS2 gene Thr21Met polymorphism and cases with diffuse or limited SSc, systemic or lung involvement, finger flexion deformity, pitting scars at the fingertips, positive anticentromere, or positive antitopoisomerase I antibody groups. Conclusion. Our study shows the association between Thr21Met, but not Ser89Asn, in the UTS2 gene and SSc. The results strongly suggest that this single-nucleotide polymorphism may be an important risk factor in the development of SSc, and a powerful indicator of severe skin and lung involvement in patients with SSc. (First Release Nov I 2011; J Rheumatol 2012;39:106-11; doi:10.3899/jrheum.110509)
Keywords: SYSTEMIC SCLEROSIS; UROTENSIN II; UROTENSIN II GENE